The comparative value of mustard seed oil meal and dehydrated brome grass meal in protein feed mixtures as a supplement to shelled corn for fattening fall pigs in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
Swine experiment I, page 43, reported the results of feeding mustard seed oil meal to fattening pigs on alfalfa pasture, when mixed with tankage and other protein supplements. Pigs were fed with protein supplement mixtures in which the mustard seed oil meal composed as much as 50 percent of the supplement. The results of feeding it in such large proportions were so satisfactory that it was desired to ascertain whether it were possible to increase further the amount of mustard seed meal in the mixture with tankage and still get good results. Consequently two lots of pigs were fed with an increased percentage of mustard seed oil meal. In addition last year in connection with some other studies there was produced at the Kansas Experiment Station some dehydrated brome grass meal. This meal had a protein content of about 20.9 percent. As there was no information at hand concerning the use and palatability of brome grass meal in swine feeding, it was thought advisable to compare it with dehydrated alfalfa meal.
Keywords: Swine; Mustard seed oil meal; Brome grass; Protein; Corn